Chromatin & Transcriptional Tango on the Immune Dance Floor - Ananda L Roy (Frontiers Research Topics, 2015)
Signaling through the cell surface antigen receptor is a hallmark of various stages of lymphocyte development and adaptive immunity. Besides the adaptive immune system, the innate immunity is equally important for protection. However, the mechanistic connection between signaling, chromatin changes and downstream transcriptional pathways in both innate and adaptive immune system remains incompletely understood in hematopoiesis. A related issue is how the enhancers communicate to the promoters in a stage specific fashion and in the context of chromatin. Because the factors that regulate chromatin are generally present and active in most cell types, how could cell type and/or stage specific chromatin architecture is achieved in response to a particular immune signal?The genetic loci that encode lymphocyte cell surface receptors are in an "unrearranged" or "germline" configuration during the early stages of development. Thus, in addition to expressing lineage and/or stage specific transcription factors during each developmental stage, lymphocytes also need to rearrange their cognate receptor loci in a strictly ordered fashion. Hence, there must be a tightly coordinated communication between the recombination machinery and the transcriptional machinery (including chromatin regulators) at every developmental step. Mature B cells also undergo classswitch recombination and somatic hypermutation. Importantly, along the way, these cells must avoid autoimmune responses and only those cells capable of recognizing foreignantigens are preserved to reach peripheral organs where they must function. The exquisite regulation that govern chromatin accessibility, recombination and transcription regulation in response to the environmental signals in the immune system is discussed here is a series of articles.